PIC Activation through Functional Interplay between Mediator and TFIIH. Issue 1 (6th January 2017) - Malik, Sohail; Molina, Henrik; Xue, Zhu
Abstract: The multiprotein Mediator coactivator complex functions in large part by controlling the formation and function of the promoter-bound preinitiation complex (PIC), which consists of RNA polymerase II and general transcription factors. However, precisely how Mediator impacts the PIC, especially post-recruitment, has remained unclear. Here, we have studied Mediator effects on basal transcription in an in vitro transcription system reconstituted from purified components. Our results reveal a close functional interplay between Mediator and TFIIH in the early stages of PIC development. We find that under conditions when TFIIH is not normally required for transcription, Mediator actually represses transcription. TFIIH, whose recruitment to the PIC is known to be facilitated by the Mediator, then acts to relieve Mediator-induced repression to generate an active form of the PIC. Gel mobility shift analyses of PICs and characterization of TFIIH preparations carrying mutant XPB translocase subunit further indicate that this relief of repression is achieved through expending energy via ATP hydrolysis, suggesting that it is coupled to TFIIH's established promoter melting activity. Our interpretation of these results is that Mediator functions as an assembly factor that facilitates PIC maturation through its various stages. Whereas the overall effect of the Mediator is to stimulate basal transcription, its initial engagement with the PIC generates a transcriptionally inert PIC intermediate, which necessitates energy expenditure to complete the process. Graphical Abstract: Highlights: Mediator regulates PIC function post-recruitment by poorly understood mechanisms. Mediator can trap the PIC in an inactive state. Mediator, TFIIH, and ATP cooperatively activate the PIC.